The Impact of Consumer Behavior and Marketing Mix on the Decision to Buy Coffee at Coffee Shops in the Sleman Region During the Covid-19 Pandemic - Alif Madya Bagas Wicaksana; Suharno Suharno; Wahyu Supartono (Agroindustrial Journal, 2022)
Coffee consumption in Indonesia has increased significantly with the increase in coffee shops. According to data obtained from the data books in 2020, coffee consumption has increased by nearly 400,000 tons. The increasing number of coffee shops in Indonesia, particularly the Sleman Regency is due to the pandemic and changes in consumer behavior. Therefore, the purpose of this research was to determine the impact of consumer behavior on the purchasing decisions at Coffee Shops based on the personal, social, psychological, and cultural factors as well as the marketing mix and its improvement during the pandemic. In this research, 10 local coffee shops in the Sleman regency were used and consumers between the ages of 17 and 27 years who had purchased coffee drink products and made transactions in the past six months were selected. The respondents comprised 157 people, and the analysis was carried out using two methods: Partial Least Square Structural Equation Modelling (PLS-SEM) and Importance Performance Analysis (IPA). PLS-SEM was used to analyze the relationship between consumer behavior factors and purchasing decisions while the IPA method was used to analyze the most effective marketing mix during the pandemic. According to the result, the factors that influence the decision to purchase coffee are the psychological factors and marketing mix while personal, cultural, and social factors had no significant effect on the coffee purchasing decisions during the pandemic. Consequently, the marketing mix that needs to be focused on is price adjustment on the drink purchased.